1975
DOI: 10.1093/jn/105.10.1351
|View full text |Cite
|
Sign up to set email alerts
|

Free Fatty Acids Identified as Antitryptic Factor in Soybeans Fermented by Rhizopus oligosporus

Abstract: The trypsin-inhibitory activity observed in cooked soybeans fermented by Rhizopus oligosporus (fungus used in tempeh fermentation) has been examined. The active compounds have now been isolated by ethanol extraction and thin-layer chromatography and have been identified as free fatty acids by infrared spectroscopy and gas-liquid chromatography. Oleic, lineoleic, and linolenic acids are primarily responsible for the increased trypsin-inhibiting activity of cooked soybeans after fermentation. The free fatty acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
4

Year Published

1979
1979
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 12 publications
1
23
0
4
Order By: Relevance
“…However, no significant differences were observed during the change of temperature. Similar reduction in TIA of fermented products including cowpeas (Ibrahim et al, 2002), Green beans (Mnkeni et al, 1996), soy (Wang et al, 1975), idli (Steinkraus, 1983), imartie (Kaul & Bajwa, 1987), black gam sprouts (Chaudhry, 1993) has also been reported. Values are mean ± SE of three independent determinations.…”
Section: Trypsin Inhibitor Activitysupporting
confidence: 53%
See 1 more Smart Citation
“…However, no significant differences were observed during the change of temperature. Similar reduction in TIA of fermented products including cowpeas (Ibrahim et al, 2002), Green beans (Mnkeni et al, 1996), soy (Wang et al, 1975), idli (Steinkraus, 1983), imartie (Kaul & Bajwa, 1987), black gam sprouts (Chaudhry, 1993) has also been reported. Values are mean ± SE of three independent determinations.…”
Section: Trypsin Inhibitor Activitysupporting
confidence: 53%
“…, 2002), Green beans (Mnkeni et al. , 1996), soy (Wang et al. , 1975), idli (Steinkraus, 1983), imartie (Kaul & Bajwa, 1987), black gam sprouts (Chaudhry, 1993) has also been reported.…”
Section: Resultsmentioning
confidence: 99%
“…Since the extraction was carried out by an 85% ethanol solvent and the antitryptic activity was assayed by Procedure I, it is assumed that the observed increased antitryptic activity was mainly due to increased production of the Ca' '-sensitive fraction during fermentation. Wang et al (1975) also observed an increase in antitryptic activity of tempeh and demonstrated that it resulted from increased production of fatty acids during fermentation. This may provide an additional indirect evidence that the Ca' +-sensitive fraction is a free fatty acid.…”
Section: Fig 3 Effect Of C a T + On The Antitryptic Activitymentioning
confidence: 83%
“…Thus, they are all capable of producing their own lipases (Tamang 1993). A negative aspect of kinemai is that FFAs can inhibit glycolytic and gluconeogenic enzymes (Weber et al 1966;Lea and Weber 1968;Pande and Mead 1968;Parvin and Dakshinamurti 1970), some hydrolases including trypsin (Bargoni 1960;Wang et al 1975;Winarno and Reddy 1986) and fatty acid synthesis (Korchak and Masoro 1964).…”
Section: Moisture Crude Lipid and Free Fatty Acidsmentioning
confidence: 99%